Pemikiran pendidikan Islam Muhammad Abduh - Ali, Muhammad Fiqri (Maliki Interdisciplinary Journal, 2024)
Islamic reform figures such as Muhammad Abduh are a blessing for Muslims. The condition of the people’s backwardness in the field of Islamic education, coupled with concerns about Western domination, makes the figure of Abduh present as a solution. He built a strong foundation of Islamic education by combining Eastern and Western styles, opening himself to Western progress without forgetting Eastern values. This is what is called modernization. Abduh played a major role in eliminating dualism in education, so that Islamic education slowly improved due to openness to knowledge from the West. In essence, the goal of Islamic education is to balance the mind and soul for goodness in this world and the hereafter.